Counseling on Starting a Healthy Life by Walking at Prolanis Cisadea Health Center: Penyuluhan Memulai Hidup Sehat Dengan Jalan Kaki Pada Prolanis Puskesmas Cisadea - Elita Hafi Dhiyah; Anita Faradilla Hakim; Dony Oktavianto (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Having a healthy and fit body is everyone's dream, especially the elderly. To maintain health and fitness, planned physical activity is needed. An activity that is very possible for elderly people to do, especially for elderly people who are less active in exercising, is light physical activity, namely walking. This activity has very little risk and is very easy to do. The aim of this counseling is to increase understanding and encourage the elderly at Cisadea Community Health Center to start physical activity to maintain health and fitness starting from light activities. The results obtained were that the counseling went well with the extension participants who had high enthusiasm for gaining new insights. The elderly's understanding of walking activities increases. It is hoped that this activity can be a start to encourage the elderly to carry out physical activity in stages, starting with light physical activity, namely walking.